Features of Women's Leadership and Nursing in Japanese Culture. - Reiko Sakashita (Asian Pacific Island Nursing Journal, 2018)
Mutual respect and harmonious relationships between people can be viewed as the fundamental spirit of Japanese culture. Japanese leaders try to keep the peace in human relations, rather than to achieve a goal. They become leaders due to internal and external conditions, rather than their own abilities. Japanese society has been basically male-dominated though the ratio of women leaders has increased recently. Higher education and development of academic societies in nursing have been very successful during the last two decades and nursing is one of the most trusted professions in Japan. However, some Japanese people still think a nurse is just an assistant to doctors. The purpose of this paper is to clarify features of women's leadership in Japan from the nursing point of view. In Japanese culture, leaders need to possess human resource leadership as an indispensable element, while good leaders may have advantages in all four frames of leadership including structural, human resource, political, and symbolic frames. Japanese organizations are also supported by excellent followership which might be influenced by the structure of Japanese society which is called "the vertical society" where leaders are fostered from among followers. What is important in Japanese leadership is to have a vision that leadership leads to the happiness of all people in a shareable form.